Effect of Artemia Nauplii Enriched with Different Kind of Lipid on the Growth and Brain Volume of Larval Tilapia Oreochromis niloticus - Dedi Jusadi; B.A. Hasyim; Ing Mokoginta (Indonesian Society of Scientific Aquaculture (ISSA), 2004)
Triplicate experiment was conducted using 4-day-old larval tilapia Oreochromis niloticus. Thirty fishes were cultured in aquarium contained 2 litres water for 14 days. During rearing period, fish were fed on Artemia nauplii enriched with fish oil, corn oil or coconut oil. It was found that brain volume of fish fed on Artemia enriched with corn oil was significantly larger than two other groups of fish. The brain volume of fish related with linoleic acid content in the diet, which was highest in Artemia enriched with corn oil. Key words: Fish oil. corn oil, coconut oil, brain, fatty acid, tilapia. Oreochromis niloticus. ABSTRAK Tiga puluh ekor larva ikan nila umur 4 hari dipelihara di dalam stoples berisi 2 1 air selama 14 hari. Selama pemeliharaan. larva diberi makan Artemia yang telah diperkaya dengan minyak ikan. minyak kelapa atau minyak jagung. Di akhir penelitian, larva ikan yang diberi makan Artemia yang diperkaya dengan minyak jagung memiliki volume otak (8,33 x 105 μm3) yang lebih besar dari otak ikan di dua perlakuan lainnya. Hal ini diduga sebagai akibat tingginya kandungan asam lemak linoleat Artemia setelah diperkaya dengan minyak jagung. Namun. perbedaan komposisi asam lemak Artemia di tiga perlakuan mempunyai pengaruh yang sama terhadap pertumbuhan larva ikan nila. Kata kunci: Minyak ikan. minyak jagung, minyak kelapa, otak, asam lemak, ikan nila, Oreochromis niloticus.